PENGARUH VOLUME DAN NOMINAL TRANSAKSI E-MONEY TERHADAP INFLASI DI INDONESIA - Ida Margareta Nainggolan; Erna Garnia (Procuratio : Jurnal Ilmiah Manajemen, 2021)
The increase in volume and nominal value of E-Money transactions during the Covid-19 pandemic was due to government policies to reduce the use of cash. This study aims to determine the effect of volume and nominal value of E-Money transactions on inflation in Indonesia. The population of this research is all transactions of E-Money products that have received permission from Bank Indonesia (BI) as of May 27, 2020. The sampling technique is using saturated sampling, where the entire population is used as the research sample. This study uses multiple linear regression with the data period January 2019 - August 2020. The results show that the volume and nominal value of E-Money transactions have a significant effect both partially and simultaneously on inflation in Indonesia. The implication of the research results is expected to become a reference for the relevant authorities in stabilizing the inflation rate. Peningkatan volume dan nominal transaksi E-Money pada masa pandemi Covid-19 dikarenakan kebijakan pemerintah untuk mengurangi pemakaian uang cash. Penelitian ini bertujuan mengetahui pengaruh volume dan nominal transaksi E-Money terhadap inflasi di Indonesia. Populasi penelitian ini adalah seluruh transaksi produk E-Money yang telah mendapat izin dari Bank Indonesia (BI) per tanggal 27 Mei 2020. Teknik penentuan sampel adalah menggunakan sampling jenuh, dimana seluruh populasi dijadikan sampel penelitian. Penelitian ini menggunakan regresi linier berganda dengan periode data Januari 2019 – Agustus 2020. Hasil penelitian menunjukkan bahwa volume dan nominal transaksi E-Money berpengaruh signifikan baik secara parsial maupun simultan terhadap inflasi di Indonesia. Implikasi hasil penelitian diharapkan dapat menjadi acuan untuk otoritas terkait dalam menstabilkan laju inflasi.